HUBUNGAN PENGETAHUAN, SIKAP, DAN VULVA HYGIENE DENGAN KEJADIAN KEPUTIHAN DI PONDOK PESANTREN BAHRUL ULUM DESA MULYASARI TAHUN 2024 - Puspita, Apriani; Fika Minata Wathan; Erma Puspita Sari; Minarti (SEKOLAH TINGGI ILMU KESEHATAN INDRAMAYU, 2025)
According to the World Health Organization (WHO), it was estimated 33% of people worldwide Vaginal discharge is a reproductive health problem that is often experienced by women, this condition will cause uncomfortable conditions and can interfere with daily activities. This study aims to determine the relationship between knowledge, attitudes, and vulva hygiene simultaneously with the incidence of vaginal discharge at Bahrul Ulum Islamic Boarding School, Mulyasari Village in 2024. The type of research is used quantitative research (data in the form of numbers) with a survey research design with a cross-sectional approach. Data collection in this study used primary data obtained from filling out questionnaires. The population in this study were 51 young women at the Bahrul Ulum Islamic Boarding School in 2024. Sampling used the total sampling technique or a sampling technique where the number of samples was the same as the population. From the 51 respondents, there were 24 respondents (47.1%) who experienced vaginal discharge and 27 respondents (52.9%) did not experience vaginal discharge. From the results of the Chi Square test, was obtained the P-Value = 1,000, which means there was no relationship between Knowledge and the Incident of Vaginal Discharge. The P-Value = 0.766 was obtained, which means there was no relationship between Attitude and the Incident of Vaginal Discharge. The P-Value value <0.000 was obtained, indicating a significant relationship between vulva hygiene and the incidence of vaginal discharge at the Bahrul Ulum Islamic Boarding School, Mulyasari Village in 2024. In addition, the results of the Odds Ratio (OR) analysis showed an OR value of 0.026 and a Confidence Interval (CI) of 95% in adolescents who experienced vaginal discharge with a value range was 0.005-0.14